Pengaruh Upah Minimum, Indeks Pembangunan Manusia dan Pengangguran Terbuka terhadap Jumlah Kemiskinan di Provinsi Bali - I D. G. M. Radityana; I K. Djayastra; A. A. N. Bagus Danendra; Ngurah Wisnu (Yayasan Pendidikan Islam Amal Shaleh Kombongan, 2023)
Poverty is defined as being trapped in a series of difficult situations that make it difficult to survive and meet the general standards of society. During the last decade, poverty has become a serious discussion both nationally and internationally. In the Province of Bali itself, poverty is something that is classified as a relatively classic problem. In general, the poverty rate in Bali Province has fluctuated both in terms of numbers and percentages. Therefore, this study was to analyze the effect of minimum wages, human development identification and open unemployment on the amount of poverty in Bali Province with the vulnerable years used from 2012 to 2021. The data source in this study is secondary data obtained from The Central Bureau of Statistics (BPS) for the Province of Bali and the UNTAB Library. The data analysis technique used in this study is the classical assumption test method, the coefficient of multiple determination, multiple linear regression, t test and F test. The results of the study show that the minimum wage has a partially significant and negative effect on poverty in the Province of Bali. The Human Development Index has a partial and significant negative effect on poverty in the Province of Bali. Open unemployment has a positive and partially significant effect on poverty in the Province of Bali. Minimum wages, human development index and open unemployment have a positive and real effect simultaneously on poverty in Bali Province